This is the way we eat our lunch : a book about children around the world - Baer, Edith (New York : Scholastic, 1995)
Relates in rhyme what children eat in countries around the world.
Keywords: Food habits -- Juvenile fiction; Manners and customs -- Juvenile fiction; Food habits -- Fiction; Manners and customs -- Fiction; nutrition education; human health; human nutrition; Habitudes alimentaires -- Romans, nouvelles, etc. pour la jeunesse; Romans, nouvelles, etc. pour la jeunesse; Food habits; Manners and customs; Eating customs -- Fiction; Manners and customs -- Fiction; Food habits-Fiction -- Manners and customs-Fiction.; Novels; novels; Fiction; Juvenile works; Fiction; Novels; Romans